2020
DOI: 10.1038/s41598-020-70738-z
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles-decorated Preyssler functionalized cellulose biocomposite as a novel and efficient catalyst for the synthesis of 2-amino-4H-pyrans and spirochromenes

Abstract: Silver nanoparticles-decorated Preyssler functionalized cellulose biocomposite (PC/AgNPs) was prepared and fully characterized by FTIR, UV–vis, SEM, and TEM techniques. The preparation of PC/AgNPs was studied systematically to optimize the processing parameters by Taguchi method using the amount of PC, reaction temperature, concentration of silver nitrate and pH of medium. Taguchi’s L9 orthogonal (4 parameters, 4 level) was used for the experimental design. The SEM analysis confirmed the presence of the Preyss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 178 publications
(131 reference statements)
0
24
0
Order By: Relevance
“…A simple and general protocol for preparation of 2-amino-4 H -pyran derivatives involves a three-component one-pot cyclocondensation of ethyl acetoacetate, malononirilel/alkyl cyanoacetate and various carbonyl compounds. Several modified methods have been reported using different homogeneous or heterogeneous catalysts such as uera-chCl 55 , potassium phthalimide- N -oxyl 56 , potassium phthalimide under ball-milling 57 , Et 3 N under sonication 54 , CuFe 2 O 4 @starch 58 , CoFe 2 O 4 -Cell/Fe (III) SSZ 59 , KF-Al 2 O 3 60 , Fe 3 O 4 /EDTA 61 , γ-Fe 2 O 3 -Im-Py) 2 WO 4 62 , amine-functionalized SiO 2 @Fe 3 O 4 63 , water extract of red mud 64 , sodium alginate 13 , 14 , isocyanurate-based periodic mesoporous organosilica 65 and silver nanoparticles-decorated Preyssler functionalized cellulose 66 in recent years. In continuation of our research group to expand the catalytic activity of pristine or modified biopolymers for different MCRs 10 14 , 32 , 67 , 68 , this report presents the use of Cs-EDTA-Cell as a biopolymer nanocatalyst for the synthesis of 2-amino-4 H -pyran derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A simple and general protocol for preparation of 2-amino-4 H -pyran derivatives involves a three-component one-pot cyclocondensation of ethyl acetoacetate, malononirilel/alkyl cyanoacetate and various carbonyl compounds. Several modified methods have been reported using different homogeneous or heterogeneous catalysts such as uera-chCl 55 , potassium phthalimide- N -oxyl 56 , potassium phthalimide under ball-milling 57 , Et 3 N under sonication 54 , CuFe 2 O 4 @starch 58 , CoFe 2 O 4 -Cell/Fe (III) SSZ 59 , KF-Al 2 O 3 60 , Fe 3 O 4 /EDTA 61 , γ-Fe 2 O 3 -Im-Py) 2 WO 4 62 , amine-functionalized SiO 2 @Fe 3 O 4 63 , water extract of red mud 64 , sodium alginate 13 , 14 , isocyanurate-based periodic mesoporous organosilica 65 and silver nanoparticles-decorated Preyssler functionalized cellulose 66 in recent years. In continuation of our research group to expand the catalytic activity of pristine or modified biopolymers for different MCRs 10 14 , 32 , 67 , 68 , this report presents the use of Cs-EDTA-Cell as a biopolymer nanocatalyst for the synthesis of 2-amino-4 H -pyran derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that homogeneous catalytic reactions have been analyzed to establish methodologies in which the use of metal nanoparticles supported onto polymers owing to their specificity towards attracting the metal nanoparticles [2,3] . Accumulation of nanoparticles over the surface of biopolymers is a leading area of research due to their potential applications in electronic devices, sensing, catalysis and bio‐medicalsciences [4] . The synthesis of metal oxide nanoparticals particularly zinc oxide nanocomposites (NCs) is an emerging research area in nanotechnology [5–7] .…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Accumulation of nanoparticles over the surface of biopolymers is a leading area of research due to their potential applications in electronic devices, sensing, catalysis and bio-medicalsciences. [4] The synthesis of metal oxide nanoparticals particularly zinc oxide nanocomposites (NCs) is an emerging research area in nanotechnology. [5][6][7] Over the years, synthesis of nanomaterials and NCs has been of great concern but there is an increasing need for the advancement of more efficient, facile and environmentally benign methods.…”
Section: Introductionmentioning
confidence: 99%
“…[33] In these reactions (domino processes), several starting materials (more than two reactants) react simultaneously and in one step at the presence of a catalyst and produce the desired product [34][35][36][37]. Multi-component reactions have unique advantages, such as the production of complex and diverse products through the formation of several bonds during an operation, without the need to isolate and purify the intermediates with high e ciency and high selectivity in the shortest time, together with the high atomic economy, therefore, they prevent the production of side and waste products during the reaction [38][39][40][41]. Polyhydroquinoline (PHQ) and 1,4-dihydropyridine (1,4-DHP) derivatives are some of the most important and oldest multicomponent reactions that were rst reported in 1882 by a German chemist named Arthur Hanztsch [42][43][44].…”
Section: Introductionmentioning
confidence: 99%